2015
DOI: 10.1007/s12529-015-9471-5
|View full text |Cite
|
Sign up to set email alerts
|

Agreeableness and Self-Consciousness as Predictors of Induced Scratching and Itch in Patients with Psoriasis

Abstract: This study showed distinct findings for PS patients and HC regarding the relationship between agreeableness and induced scratching. The relationship between public self-consciousness and induced itch was positive in both groups. The distinct finding regarding agreeableness supports the idea that scoring low on this scale might be a protective factor for scratching in PS patients. Future research should investigate mediating factors of the outlined relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 30 publications
4
38
2
3
Order By: Relevance
“…[ 39,40 ] . Ferner konnte gezeigt werden, dass Stimmungen wie Ängstlichkeit oder Depressivität [ 41 ] sowie bestimmte Persönlichkeitseigenschaften wie "Neurotizismus" (im Sinne emotionaler Instabilität als Tendenz, mehr negative Emotionen zu erleben) [ 42 ] , geringere Verträglichkeit, Gehemmtheit [ 41 ] und niedriges Selbstwirksamkeitserleben [ 43 ] Zusammenhänge zu einer stärkeren Ausprägung der Ferner konnte gezeigt werden, dass Stimmungen wie Ängstlichkeit oder Depressivität [ 41 ] sowie bestimmte Persönlichkeitseigenschaften wie "Neurotizismus" (im Sinne emotionaler Instabilität als Tendenz, mehr negative Emotionen zu erleben) [ 42 ] , geringere Verträglichkeit, Gehemmtheit [ 41 ] und niedriges Selbstwirksamkeitserleben [ 43 ] Zusammenhänge zu einer stärkeren Ausprägung der…”
Section: Empfehlungunclassified
“…[ 39,40 ] . Ferner konnte gezeigt werden, dass Stimmungen wie Ängstlichkeit oder Depressivität [ 41 ] sowie bestimmte Persönlichkeitseigenschaften wie "Neurotizismus" (im Sinne emotionaler Instabilität als Tendenz, mehr negative Emotionen zu erleben) [ 42 ] , geringere Verträglichkeit, Gehemmtheit [ 41 ] und niedriges Selbstwirksamkeitserleben [ 43 ] Zusammenhänge zu einer stärkeren Ausprägung der Ferner konnte gezeigt werden, dass Stimmungen wie Ängstlichkeit oder Depressivität [ 41 ] sowie bestimmte Persönlichkeitseigenschaften wie "Neurotizismus" (im Sinne emotionaler Instabilität als Tendenz, mehr negative Emotionen zu erleben) [ 42 ] , geringere Verträglichkeit, Gehemmtheit [ 41 ] und niedriges Selbstwirksamkeitserleben [ 43 ] Zusammenhänge zu einer stärkeren Ausprägung der…”
Section: Empfehlungunclassified
“…However, also the presentation of certain (audio-) visual stimulus material has repeatedly been shown to induce itch. By now there are several studies, which found that the presentation of itch-related stimuli, like pictures of crawling insects or videos showing other people scratching, can trigger itch and scratch responses in both healthy subjects and patients with chronic itch (Niemeier et al, 2000; Papoiu et al, 2011b; Lloyd et al, 2013; Schut et al, 2014, 2015b). However, so far there are only two studies, which investigated brain activity induced by such itch related stimuli (Holle et al, 2012; Mochizuki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize that the extent to which subjects react to itch stimuli does not only depend on the itch stimulus (e.g. Kodama et al, 1999;Verhoeven et al, 2008;Van Laarhoven et al, 2011;Schut and Kupfer, 2013;Schut et al, 2014Schut et al, , 2015b. In a study in which histamine was used to induce itch, mood was an important factor influencing the intensity of the reaction to itch stimuli (Van Laarhoven et al, 2012): Women in a positive emotional state reported less intense itch than women who had negative emotions.…”
Section: The Itch Sensation and Its Provocation By Audiovisual Stimulimentioning
confidence: 99%
“…cowhage or histamine, Papoiu et al, 2011a) but also on the psychological status of the subjects. This review focuses on personality and expectations as psychological factors related to itch induced by (audio-) visual stimuli (Holle et al, 2012;Schut et al, 2014Schut et al, , 2015b. Besides, mood, also other psychological factors like stress, itch-related cognitions, personality and expectations towards itch stimuli have been shown to be associated with itch sensations in healthy subjects and patients with itchy skin diseases (e.g.…”
Section: The Itch Sensation and Its Provocation By Audiovisual Stimulimentioning
confidence: 99%
See 1 more Smart Citation